Sebuah Kisah Ayub dalam perspektif psikoanalisis: Sebuah Kajian Teologi Biblis-Kontekstual bagi masyarakat yang terdampak Kerusuhan Ambon 1999 - Claudie Valda Silooy (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
The riots in Ambon in 1999 are studied based on the story of the figure of Job who experienced trials in a barrage in the book of Ayub. These two different contexts will generate a new perspective to interpret the concept of suffering. In this effort, the author uses qualitative research with a psychoanalytic perspective from Sigmund Freud to show the spirituality of people who experience suffering. This article aims to analyze the psychological condition as well as the behavioral changes resulting from these two events, as well as contribute contextual theology to the sufferer. On the other hand, this article also discusses the study of trauma and theological concerns in trauma issues to understand the people in Ambon who felt the impact of the riots. This paper is presented with the aim of looking at changes in human behavior in the context of suffering, and helping readers to understand that suffering is not an avoidable thing. One of the keys to the suffering that man must do is to live it with confidence and hope in God.